2018
DOI: 10.1111/soru.12221
|View full text |Cite
|
Sign up to set email alerts
|

Openness to Social Science Knowledges? The Politics of Disciplinary Collaboration within the Field of UK Food Security Research

Abstract: This article explores a form of knowledge politics played out within and between universities and research institutes as sites of certified disciplinary expertise in the agro‐food domain. It investigates the openness of this domain to the expertise of the agro‐food social sciences particularly when challenge‐led research programmes require collaboration across disciplines. A case study is provided by the multi‐discipline field of food security research in the UK involving interviews with key stakeholders. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Bringing other forms of expertise and experience to bear on the environmental dimension of AMR is therefore an important task within future work. In doing so, work on the research field of AMR and the environment is 'opened up' (Morris et al, 2019). That a move towards this is already happening is evidenced in UKRI's AMR research programme which requires a multi-disciplinary approach in the projects it funds.…”
Section: Opening Up the Field Of Environmental Amrmentioning
confidence: 99%
“…Bringing other forms of expertise and experience to bear on the environmental dimension of AMR is therefore an important task within future work. In doing so, work on the research field of AMR and the environment is 'opened up' (Morris et al, 2019). That a move towards this is already happening is evidenced in UKRI's AMR research programme which requires a multi-disciplinary approach in the projects it funds.…”
Section: Opening Up the Field Of Environmental Amrmentioning
confidence: 99%
“…In this paper, we have described a research prioritisation process that was designed to develop capacity, mutual understanding and impact amongst researchers within the social sciences and humanities and to help coordinate research effort to address the societal grand challenge of moving beyond animal-based food systems. The process focused deliberately upon social sciences and humanities researchers in recognition of the more generally observed problem of selective openness to these disciplines within multi-discipline research programmes designed to address societal grand challenges (Morris et al, 2019). Organising the process in this way proved extremely worthwhile as it provided a dedicated space in which scholars had the freedom to identify collectively the most important research questions from their perspectives at a time when research funders are slowly beginning to acknowledge the need for research in this domain.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is not a blanket recommendation. As Morris et al (2019) argue inter/trans-disciplinarity should always be approached critically even though this challenges dominant research governance discourses which naturalise these ways of producing knowledge. Whether the reframing of the topic as described here is suitable for the purposes of engaging a wider group of participants, or whether an alternative, less obviously contentious framing is needed is another matter to which the designers of future prioritisation exercises will need to pay close attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Datta's (2018) experience on an interdisciplinary project, he found that respect, trust, vulnerability, attentiveness to others' feelings, professional flexibility, timely leadership, and courage were essential to a successful outcome. Adequately addressing these issues can be particularly challenging for many researchers, given the power asymmetries between different disciplines (Morris et al, 2019) and between academic ranks.…”
Section: Introductionmentioning
confidence: 99%